THE CREATIVE ECONOMY ON THE ENVIRONMENTAL OF THE TECHNOLOGICAL PARKS AND INCUBATORS - Inglesis Barcellos, Ekaterina Emmanuil [UNESP]; Botura Junior, Galdenoro [UNESP]; Sanz Ramirez, Claudia Marcela (Univ Nove Julho, 2016)
The creative economy has become a key element in generating ideas, products and services being an evolving concept based on creative assets, which modifies the profile of industry and global market, from the partnership between creativity and economics combined with innovation and technology. In Brazil, Technological Parks and Incubators, in turn, have not devoted themselves with real interest in this emerging sector; they are involved primarily with technologies for areas such as biotechnology, environment, embedded electronics, alternative energy, oil, software and, mainly, IT (ICT). This article identifies how the economy and creative industry have changed the entrepreneurial profile in the national and global environment and how these trends are applicable in relation to the environment of the Parks and Incubators for the inclusion of creativity in the current Brazilian scenario. Shows that the creative production promotes skills that constitute the knowledge of Design, Architecture, Cultural Heritage, Media, Culture and Arts, acting democratically, adding knowledge, diversity and differentiation, overcoming social and regional barriers and making social inclusion. It shows that a market segment that involved about US $ 624 billion in 2011, more than doubling between 2002 and 2011, maintains a growth trajectory has only 2% of the featured activities of the Parks aimed at its development and promotion.
Keywords: Creative Economy; Design; Innovation; Technological Parks